A new Miocene fern (Palaeosorum: Polypodiaceae) from New Zealand bearing in situ spores of Polypodiisporites. Issue 1 (2nd January 2019) - Kaulfuss, Uwe; Conran, John G.; Bannister, Jennifer M.; Mildenhall, Dallas C.; Lee, Daphne E.
ABSTRACT: A new species of fossil fern with in situ spores, Palaeosorum waipiata (Polypodiaceae), is described and figured for a microsoroid fern frond from earliest Miocene sediments in Otago, New Zealand. The fertile frond from the Foulden Maar fossil Lagerstätte is pinnatifid with deep narrow lobes with entire margins and bears circular sori without indusia in rows on either side of the lobe midrib. Monolete spores associated with the frond are differentiated from similar, widespread dispersed spores of Polypodiisporites radiatus in possessing very small proximal verrucae/granulae around the laesurae and more rounded verrucae and the description of Palaeosorum is expanded to include information about sori and spores. This is the first confident Southern Hemisphere record for a microsoroid fern macrofossil, as well as the first with in situ spores. It is probable that this fern was epiphytic on trees or lithophytic on rocks adjacent to the Miocene maar lake.